“Голомт" хийгээд "Голомдох"-ын учир - Ж.Ганбаатар, (Acta Mongolica, 2013)
In this article, the etymology of Mongolian word"yolomf' is studied.This word has been analyzed from linguists point of view. The structure of yol-(u)mta and word root has been explained in connection with '*уаl'(fire) and*үоl' (сеnter) meanings. As a result of this study, it is ascertained that the word root is *kul. In earlier time, *kul root shows hot ash. *kulum/*qulum/yolum means the burned trace of fire, yolumtu(mo.yolumla) shows the place around ashy stove. Furthermore,"Yolomt**named fire, home, heir and family of the ancestor. Later, it means as"spot,nucleus.Formation*'. which is developed from main word.